2006
DOI: 10.1063/1.2336486
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz photonic mixers as local oscillators for hot electron bolometer and superconductor-insulator-superconductor astronomical receivers

Abstract: A pump experiment of two astronomical heterodyne receivers, a superconductorinsulator-superconductor ͑SIS͒ receiver at 450 GHz and a hot-electron-bolometer ͑HEB͒ receiver at 750 GHz, is reported. A low-temperature-grown GaAs metal-semiconductor-metal photonic local oscillator ͑LO͒ was illuminated by two near infrared semiconductor lasers, generating a beat frequency in the submillimeter range. I-V junction characteristics for different LO pump power levels demonstrate that the power delivered by the photomixer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…With the rapid advancement of QCLs, they will play a critical role in the future heterodyne terahertz detection system. Photomixers, which use two lasers beams with a terahertz beat frequency to modulate the carrier concentration in an antenna-coupled photoconductor, have also been used to pump HEB mixers and SIS mixers [121][122][123]. For example, a photomixer with an integrated dual-dipole antenna ( gure 11(a)) has been used to pump SIS mixers at 1.05 THz in the heterodyne receiver of the APEX telescope.…”
Section: Local Oscillatorsmentioning
confidence: 99%
“…With the rapid advancement of QCLs, they will play a critical role in the future heterodyne terahertz detection system. Photomixers, which use two lasers beams with a terahertz beat frequency to modulate the carrier concentration in an antenna-coupled photoconductor, have also been used to pump HEB mixers and SIS mixers [121][122][123]. For example, a photomixer with an integrated dual-dipole antenna ( gure 11(a)) has been used to pump SIS mixers at 1.05 THz in the heterodyne receiver of the APEX telescope.…”
Section: Local Oscillatorsmentioning
confidence: 99%
“…The edge transition superconductive bolometers have been investigated in various studies (Skchez et al, 1997;Fardmanesh, 2004;Cámara Mayorgaa et al, 2006). Photo-mixing devices needed for hot electron bolometers, which have been verified with a superconductor-insulator-superconductor (SIS) mixer, have tremendous potential for various applications such as radio astronomy, terahertz imaging, high-resolution www.intechopen.com spectroscopy, medicine, security, and defense (Cámara Mayorgaa et al, 2006). Moreover, it has been reported that the design, fabrication and performance of a high temperature GdBa 2 Cu 3 0 7-x , superconductor bolometer positioned on a thick silicon nitride membrane.…”
Section: Bolometer Applications Of High Temperature Superconductorsmentioning
confidence: 99%
“…Another reason for the use of this type of substrate is that no power is lost in surface modes [3]. The substrate with the photomixer device is usually glued to the substrate lens whose dielectric constant is chosen to be similar to that of the photomixer substrate (which is usually a III-V compound semiconductor [4,5]). This fact avoids reflection in the interface between both media.…”
Section: Introductionmentioning
confidence: 99%